PELATIHAN PEMBUATAN KOMPOS MENGGUNAKAN EFFECTIVE MICROORGANISMS (EM4) BAGI GURU-GURU SD NEGERI 18 PEKANBARU - Asyti Febliza; Zul Afdal; Oktariani Oktariani (Jurnal Pengabdian UntukMu NegeRI, 2019)
Public Elementary School 18 Pekanbaru is one of autonomous adiwiyata school in 2012. The program done in this school is compost production. However, this act had not used effective microorganisms (EM4) so it caused more time consuming and ineffective for plants fertilizer. To overcome this problem, volunteer team conducted compost production training by using effective microorganisms (EM4) for teachers in Public Elementary School 18 Pekanbaru. The purpose of this activity is to increase teachers’ knowledge about making compost by adding effective microorganisms (EM4). Demonstration and practice method was used in this activity. This program was conducted for two days in which the first day for delivering theory information and demonstration/practice about impulse sealer utilization. In the second day was conducted compost production training by using EM4. This activity located in Public Elementary School 18 Pekanbaru was conducted in several steps, namely: preparation step, implementation step, and evaluation step. Based on evaluation questionnaire result which was given to Public Elementary School 18 Pekanbaru teachers obtained information that approximately 72,7% teachers’ knowledge increased after training activity.